Multi-stage treatment for Spetzler-Martin grades III, IV, and V arteriovenous malformations: preoperative embolization and microsurgical resection in a consecutive series of 250 patients - Alfter, Marcel; Albiña-Palmarola, Pablo; Cimpoca, Alexandru; Díaz-Peregrino, Roberto; Jans, Paul; Ganslandt, Oliver; Kühne, Dietmar; Henkes, Hans (Journal of Clinical Medicine, 2023)
Purpose. The treatment of high-grade brain AVMs is challenging and has no guidelines available to date. This study was aimed at reporting the experience of two centers in treating these AVMs through a multi-stage approach consisting of preoperative embolization and microsurgical resection. Methods. A retrospective review was performed for 250 consecutive patients with a diagnosis of high-grade brain AVM (Spetzler-Martin grades III, IV, and V) treated in two centers in Germany between January 1989 and February 2023. The analyzed data included demographic, clinical, morphological, and neurological data. Results. A total of 150 cases (60%) were classified as Spetzler-Martin grade III, 82 cases (32.8%) were classified as grade IV, and 18 cases (7.2%) were classified as grade V. Eighty-seven cases (34.8%) presented with hemorrhage. The devascularization percentages achieved were <50% in 24 (9.6%), 50-80% in 55 (22%), and >80% in 171 (68.4%) cases. The average number of sessions was 5.65 ± 5.50 and 1.11 ± 0.32 endovascular and surgical procedures, respectively, and did not significantly differ by rupture status. Death or dependency (mRS score ≥ 3) after the last follow-up was observed in 18.8% of patients and was significantly associated with age > 80 years and poor baseline neurological condition. The complete resection rate was 82.3% and was significantly associated with age > 80 years, large nidus, and deep venous drainage. Permanent disabling neurological deficit after at least 3 months of follow-up was diagnosed in 13.2% of patients and was significantly associated with age > 80 years and infratentorial locations. Conclusion. A multi-stage treatment for high-grade AVMs is feasible for selected cases but comes at a functional cost. The devascularization percentage was not associated with the investigated outcomes. Age > 80 years was associated with poor safety and effectiveness outcomes; consequently, this treatment should be offered only in exceptional circumstances.
Gesehen am 05.12.2023